Carbon nanodots prepared from NaOH-boiled graphene and its usage as a support of PdO for ethanol oxidation reaction. (13th April 2017) - Ding, Keqiang; Wang, Pingyuan; Zhao, Jing; Li, Yuan; Chen, Yuying; Zhang, Yan; Wei, Binjuan; Sun, Yanzhi; Pan, Junqing
Abstract: For the first time, carbon nanodots were prepared from NaOH-boiled graphene. And, a novel catalyst that contained PdO and carbon nanodots (denoted as PdO/CND) was fabricated in this work. In this work, 0.5 M and 1.5 M NaOH solutions were respectively employed with an intention to study the influence of NaOH concentration on the electrocatalytic activity of the obtained catalysts for ethanol oxidation reaction (EOR). The obtained samples were thoroughly characterized using X-ray diffraction (XRD), transmission electron microscopy (TEM) and fourier transform infrared spectrometry (FTIR). The results indicated that the intensities of the diffraction peaks for graphene were significantly promoted with increasing the NaOH concentration and carbon nanodots with an average particle size less than 4 nm were fabricated by this developed boiling–grinding–ultrasonication (BGU) method. The electrocatalytic performances of the obtained PdO/CND catalysts for EOR were investigated using cyclic voltammetry (CV) and chronoamperometry (CA). And the consequences strongly demonstrated that PdO/CND prepared from 0.5 M NaOH-boiled graphene showed the best electrocatalytic activity towards EOR among all the prepared catalysts. Developing a very facile method for producing carbon nanodots as well as a novel composite catalyst that contained PdO and carbon nanodots for EOR was the main contribution of this work. Highlights: Carbon nanodots were prepared from NaOH-boiled graphene. The composite of PdO/CND showed electrocatalytic activity towards EOR. The catalyst of PdO/CND-0.5M delivered the best electrocatalytic activity for EOR.